2020
DOI: 10.1177/0886260519898437
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life Following Intimate Partner Psychological Aggression: The Roles of Self-Kindness, Positive Reframing, and Growth

Abstract: Psychological aggression is experienced by a large proportion of people in intimate relationships, and the negative impact of this experience has the potential to weaken one’s sense of meaning in life. This study aimed to understand a mechanism through which the experience of psychological aggression in a past intimate relationship relates to less meaning in life. By applying self-compassion and meaning-making theory, we proposed that the experience of psychological aggression decreases one’s ability to be kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Psychological aggression is the most common form of IPV and is an even stronger predictor of PTSD than physical violence. Psychological violence is likely to reduce self-kindness and is thus related to less meaning in life, less positive reframing of stressful events, and result in less growth and maturity in the victim of IPV [17]. Victims of IPV also often lose their internal ego structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological aggression is the most common form of IPV and is an even stronger predictor of PTSD than physical violence. Psychological violence is likely to reduce self-kindness and is thus related to less meaning in life, less positive reframing of stressful events, and result in less growth and maturity in the victim of IPV [17]. Victims of IPV also often lose their internal ego structure [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these aforementioned findings, we assumed that ACEs positively influenced CPTSD symptoms through the mediating effects of self-judgement. Clinically, self-kindness and selfjudgement are important interventions when treating individuals with ACEs (Naismith, Zarate, & Feigenbaum, 2019;Samios et al, 2020) and CPTSD (Karatzias et al, 2019). Empirically, however, the mediating effects of self-kindness and self-judgement on ACEs and CPTSD symptoms have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an investigation conducted on survivors of the 2010 eruption of Mount Merapi, in which most of the subjects were female, showed that meaning-in-life was negatively correlated with mental health problems (Noviana & Iwasaki, 2019). Samios et al (2020) investigated meaning-in-life following IPV considering the role of self-kindness, positive reframing, and growth. their results indicated that the more severe experienced psychological violence was correlated with low self-kindness, which in turn was associated with less positive reframing, that was sequentially linked with diminished growth, and was linked with decreased meaning-in-life as well.…”
Section: Introductionmentioning
confidence: 99%